Changes in the exclusion criteria in a clinical trial about arterial catheters patency - Núria Grané Mascarell; Mercedes del Cotillo Fuente; Maria Llavoré Fàbregas; Salvador Quintana Riera (Fundación para el Desarrollo de la Enfermería, 2005)
Regarding a clinical trial designed to compare the functionality of arterial catheters kept with heparin vs saline solution, a slow rate of case recruiting was detected. In order to improve this rate an analysis of the reasons for non-inclusion was set up. According to the results, amendments to the protocol had to be proposed to improve case inclusion without reducing the quality of the study.Methodology: All not included catheter insertions were registered and analysed regarding the reason of non-inclusion.Results: The more frequent reasons for non including a case in the study were the insertion of the catheter in other ward or department, the issues related with the informed consent (IC) and the need of more than 5 attempts to insert the catheter. The remaining reasons were related to hematological issues as well as competition with other trials.Conclusions: The main reasons for not including cases in the trial were subject to be changed by including amendments to the protocol, without affecting neither the trial quality nor the proposed goals. So, four amendments were proposed to the local ethical commission, two of which were accepted and subsequently notified to the Spanish Drug Agency. The phase of cases inclusion is now ending with less delay had the amendments not been presented.